2017
DOI: 10.1159/000455044
|View full text |Cite
|
Sign up to set email alerts
|

Venous Air Embolism during Hysteroscopic Myomectomy: An Analysis of 7 Cases

Abstract: Venous air embolism (VAE) is a rare but potentially fatal complication of hysteroscopic myomectomy. The symptoms of VAE range from mild and clinically insignificant to complete cardiovascular collapse during surgery. Anesthesiologists and surgeons should be aware of the clinical characteristics and predisposing factors of this possible adverse event. This report analyzes 7 cases of VAE, which occurred at the University Hospitals Leuven, in patients undergoing hysteroscopic myomectomy from April 2009 to April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Further short-term complications, such as excess fluid absorption, pulmonary edema, critical electrolyte disbalance, or genital tract burns, and long-term consequences (intrauterine adhesions) should be mentioned [54][55][56]. Venous air embolism during endometrial resection/endometrial ablation (ER/EA) or hysteroscopic myomectomy, although exceedingly rare (1:1140 surgeries), is a potentially fatal complication [57,58]. Myomectomies are hysteroscopic procedures with the highest complication rate (up to 14%) and the highest risk of distension medium-related complications (more than seven times more common compared to polypectomy) [54].…”
Section: Operative Hysteroscopymentioning
confidence: 99%
“…Further short-term complications, such as excess fluid absorption, pulmonary edema, critical electrolyte disbalance, or genital tract burns, and long-term consequences (intrauterine adhesions) should be mentioned [54][55][56]. Venous air embolism during endometrial resection/endometrial ablation (ER/EA) or hysteroscopic myomectomy, although exceedingly rare (1:1140 surgeries), is a potentially fatal complication [57,58]. Myomectomies are hysteroscopic procedures with the highest complication rate (up to 14%) and the highest risk of distension medium-related complications (more than seven times more common compared to polypectomy) [54].…”
Section: Operative Hysteroscopymentioning
confidence: 99%
“…If available, inotropic and vasopressor support (such as norepinephrine) can maintain hemodynamic stability and organ perfusion. 27 Further management of VAE would take place in the inpatient setting. If hemodynamic instability persists and air lock of the right ventricular outflow tract is suspected, consider right-sided central line placement to aspirate air from the right ventricle.…”
Section: Planmentioning
confidence: 99%
“…Intravenous fluids should run open to increase central venous pressure. If available, inotropic and vasopressor support (such as norepinephrine) can maintain hemodynamic stability and organ perfusion 27 …”
Section: Clinical Scenariosmentioning
confidence: 99%
“…20 During myomectomy, central enucleation should be performed, rather than opening the capsule of the myoma, thereby reducing the length of time the uterine veins are distended. 21 In addition, it has been recommended that the removal and reintroduction of the hysteroscope should be kept to a minimum. 18 Previously it has been concluded that the risk of gas embolism increases proportionally with increasing intravasation, 4 and there have been studies that have shown that injection of vasopressin paracervically reduces the degree of intravasation 7,8 as well as reduced blood loss and operating time.…”
Section: Preventionmentioning
confidence: 99%